Assessment Of Knowledge, Attitude and Practice Regarding Self -Ear Cleaning Among Medical Students in A Tertiary Care Centre - P M, Gokul; Paul, Indranil; B, Monesha (Journal of Neonatal Surgery, 2025)
Background: Self-ear cleaning is a commonly practiced habit influenced by cultural beliefs and misconceptions about ear hygiene. Even medical students, who are expected to promote safe health behaviours, may unknowingly adopt unsafe ear-cleaning methods. This study evaluates the knowledge, attitudes, and practices (KAP) related to self-ear cleaning among undergraduate medical students. Aims & Objectives: To assess knowledge, attitude and practice regarding self-ear cleaning among undergraduate (MBBS) students Methods: A descriptive cross-sectional study was conducted between April and May 2025 involving 399 undergraduate MBBS students, including interns, at a tertiary care teaching hospital in rural India. Data were collected using a structured, self-administered questionnaire covering demographic details and specific KAP components. Statistical analysis included Z-tests and ANOVA for quantitative data, and Chi-square tests for categorical variables, with significance set at p < 0.05 Results: A total of 399 students participated in the study, comprising 224 males (56.1%) and 175 females (43.9%). The majority (92.7%) reported cleaning their ears occasionally, with cotton buds being the most frequently used item (88%). Although 69.9% acknowledged the potential for injury from cotton buds, 45.1% still believed self-ear cleaning was beneficial. Nearly half (49.1%) had engaged in the practice for more than ten years. Reported complications included earache (34.1%), bleeding (5.0%), and otitis externa (4.0%). Despite awareness of associated risks, many participants continued to favor the use of ear-cleaning tools, highlighting a disconnect between knowledge and behavior. Conclusion: The findings reveal a significant gap between awareness and practice regarding self-ear cleaning among medical students. Despite adequate knowledge of the risks, unsafe behaviors remain prevalent. This underscores the need to incorporate focused ear health education into undergraduate medical training to promote safer practices and prepare students to educate others effectively.